The effect of staged projekt management on product innovation: Evidence from a firm survey - Shoko Haneda; Koki Kurihara; Arito Ono (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
This study examines whether staged project management is beneficial or harmful for making product innovations. Using a unique firm urvey for Japan, we find that firms that employed staged project management had a higher likelihood of introducing new products to the market. Additional estimations show that the positive effect of staged project management on product innovation is stronger when firms provided feedback at the interim stages. In contrast, whether and how firms set milestones was not associated with the likelihood of product innovation. The marginal effect of feedback was larger for new-to-market product innovation than for new-to-firm product innovation, and the feedback from non-R&D organizations within the firm in the initial stages was particularly beneficial for the introduction of new-to-market products. Our findings suggest that staged project management is beneficial for product innovation, but its effectiveness depends on how firms set milestones and feedback as well as the nature of innovation.
Keywords: D22; G32; M11; O31; O32; 330; staged project management; product innovation; milestones; feedback; exploration; exploitation